Feasibility and cost analysis of implementing high intensity aphasia clinics within a sub-acute setting. (June 2014) - Wenke, Rachel; Lawrie, Melissa; Hobson, Tania; Comben, Wendy; Romano, Michelle; Ward, Elizabeth; Cardell, Elizabeth
Abstract: The current study explored the clinical feasibility and costs of embedding three different intensive service delivery models for aphasia treatment (computer, group therapy, and therapy with a speech pathology therapy assistant) within three sub-acute facilities. The study employed a two cohort comparison design, with the first cohort ( n = 22) receiving the standard service of treatment currently offered. This treatment was delivered by a speech-language pathologist and involved on average 3 hours of treatment/week over 8 weeks. Participants in the second cohort ( n = 31) received one of the three intensive treatment models providing up to 9 hours of therapy/week for 11 weeks. Organizational data was collected throughout treatment, with participant, caregiver, and clinician satisfaction with the intensive models also being measured. Participants completed the spoken language production sub-tests and the Disability Questionnaire of the Comprehensive Aphasia Test (CAT) pre- and post-treatment. All intensive models yielded high participant attendance, satisfaction, and significant improvements to the CAT sub-tests. The pro-rata cost of providing treatment per hour per client for the computer and group therapy models was found to be ˜ 30% cheaper compared to the standard service. The outcomes support the potential feasibility of embedding the different models into sub-acute facilities to enhance client access to intensive treatment for aphasia.